2018
DOI: 10.1136/jnnp-2018-318800
|View full text |Cite
|
Sign up to set email alerts
|

Story of the ALS-FTD continuum retold: rather two distinct entities

Abstract: ObjectiveTo determine the evolution and profile of cognitive and behavioural deficits in amyotrophic lateral sclerosis (ALS) and behavioural variant frontotemporal dementia (bvFTD) to disentangle the development of FTD in ALS and vice versa.MethodsIn a prospective design, cognitive and behavioural profiles of 762 patients with motor predominant ALS (flail arm/leg syndrome, primary lateral sclerosis, pseudobulbar palsy, ALS) and behavioural predominant FTD (bvFTD, ALS-FTD) were determined and caregivers of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
(21 reference statements)
1
23
0
1
Order By: Relevance
“…For example, the relevance given to apathy in the diagnosis of ALSbi could indeed reduce the specificity of the criteria, considering the complexity of the theoretical construct of this particular behaviour23 and of its neuroanatomical and cognitive substrates 24. However, it should be noted that in a study based on ECAS, apathy was the most common behavioural symptoms detected in patients with ALS compared with patients with FTD, in whom disinhibition predominated 25. Longitudinal studies evaluating the progression over time of such patients are necessary to rule out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the relevance given to apathy in the diagnosis of ALSbi could indeed reduce the specificity of the criteria, considering the complexity of the theoretical construct of this particular behaviour23 and of its neuroanatomical and cognitive substrates 24. However, it should be noted that in a study based on ECAS, apathy was the most common behavioural symptoms detected in patients with ALS compared with patients with FTD, in whom disinhibition predominated 25. Longitudinal studies evaluating the progression over time of such patients are necessary to rule out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Such convergent evidence supports the notion of a spectrum or continuum of disease. 3 10 On the other hand, some authors 11 have reported distinct cognitive profiles in ALS and ALS-FTD, and explicitly argue against the notion of a continuum. Moreover, while FTD-ALS is pathologically homogenous, invariably being associated with TDP-43 pathology, 5 half of FTD cases without ALS have alternative pathologies: tau or fused-in-sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive function may be impaired in up to 50% of ALS patients in various degrees up to full blown (mostly behavioural variant) frontotemporal dementia (5%–15% of cases); in the former patients, about half of them show deficits in one cognitive domain only, for example, in executive, language or fluency function 3. The pattern of neurocognitive changes in ALS has been described consistently in several studies but it is poorly understood how these cognitive changes are associated with brain pathology in ALS.…”
Section: The Thought-provoking Hypothesis Has Been Empirically Testedmentioning
confidence: 99%